The impact of the Adolescent Girls Empowerment Program (AGEP) on short and long term social, economic, education and fertility outcomes: a cluster randomized controlled trial in Zambia - Austrian, Karen (BMC Public Health, 2020)
BACKGROUND: Adolescent girls in Zambia face risks and vulnerabilities that challenge their healthy development into young women: early marriage and childbearing, sexual and gender-based violence, unintended pregnancy and HIV. The Adolescent Girls Empowerment Program (AGEP) was designed to address these challenges by building girls’ social, health and economic assets in the short term and improving sexual behavior, early marriage, pregnancy and education in the longer term. The two-year intervention included weekly, mentor-led, girls group meetings on health, life skills and financial education. Additional intervention components included a health voucher redeemable for general wellness and reproductive health services and an adolescent-friendly savings account. METHODS: A cluster-randomized-controlled trial with longitudinal observations evaluated the impact of AGEP on key indicators immediately and two years after program end. Baseline data were collected from never-married adolescent girls in 120 intervention clusters (3515 girls) and 40 control clusters (1146 girls) and again two and four years later. An intent-to-treat analysis assessed the impact of AGEP on girls’ social, health and economic assets, sexual behaviors, education and fertility outcomes. A treatment-on-the-treated analysis using two-stage, instrumental variables regression was also conducted to assess program impact for those who participated. RESULTS: The intervention had modest, positive impacts on sexual and reproductive health knowledge after two and four years, financial literacy after two years, savings behavior after two and four years, self-efficacy after four years and transactional sex after two and four years. There was no effect of AGEP on the primary education or fertility outcomes, nor on norms regarding gender equity, acceptability of intimate partner violence and HIV knowledge. CONCLUSIONS: Although the intervention led to sustained change in a small number of individual outcomes, overall, the intervention did not lead to girls acquiring a comprehensive set of social, health and economic assets, or change their educational and fertility outcomes. It is important to explore additional interventions that may be needed for the most vulnerable girls, particularly those that address household economic conditions. Additional attention should be given to the social and economic environment in which girls are living. TRIAL REGISTRATION: ISRCTN29322231. Trial Registration Date: March 04, 2016; retrospectively registered.